2020
DOI: 10.6065/apem.1938154.077
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of growth hormone therapy in children with Noonan syndrome

Abstract: Purpose: Recombinant human growth hormone (rhGH) has been used to improve growth in children with Noonan syndrome (NS). This study aimed to investigate the efficacy of rhGH therapy in Korean children with NS. Methods: Seventeen prepubertal children (10 boys, 7 girls) with NS who received rhGH therapy for at least 3 years between 2008 and 2017 were included. To compare the response, age-and sex-matched children with GH deficiency (GHD; n=31) were included. Height and growth velocity before and during treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Similar results have been reported by Tamburrino et al in a cohort of patients affected by RASopathies (25). Furthermore, Seok et al demonstrated an increase of HSDS and GV after 3 years of treatment in prepubertal NS children, with a similar response between NS and GHD patients (32). Malaquias et al in a cohort of NS PTPN11 + patients demonstrated the benefits of rhGh therapy on AH, compared with a small cohort of PTPN11− subjects (33).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results have been reported by Tamburrino et al in a cohort of patients affected by RASopathies (25). Furthermore, Seok et al demonstrated an increase of HSDS and GV after 3 years of treatment in prepubertal NS children, with a similar response between NS and GHD patients (32). Malaquias et al in a cohort of NS PTPN11 + patients demonstrated the benefits of rhGh therapy on AH, compared with a small cohort of PTPN11− subjects (33).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, Seok et al. demonstrated an increase of HSDS and GV after 3 years of treatment in prepubertal NS children, with a similar response between NS and GHD patients ( 32 ). Malaquias et al.…”
Section: Discussionmentioning
confidence: 90%
“…Up to 70% of NS subjects present with postnatal short stature ( 17 , 37 ), even though the majority has a normal birth weight and length ( 20 ); the presence of edema may result in an overestimation of weight which should be carefully evaluated ( 20 ). Some authors have reported a significantly higher frequency of NS subjects who are small for gestational age (SGA) compared with the general population (24%), particularly for length ( 24 ), and in specific genotypes ( 24 , 38 ). Attention should be paid to SGA patients whose phenotypic characteristics are suggestive of a RASopathy, and to children who do not respond to GH treatment ( 39 ).…”
Section: Growth and Growth Hormone-igf-1 Axis In Noonan Syndromementioning
confidence: 99%
“…Side effects in children were infrequently reported. Based on the data, rhGH treatment does not seem to influence cardiac physiology and function ( 38 ). The decision to use rhGH in patients with NS should, however, be made on a case-by-case basis ( 8 ).…”
Section: Overview Of Cautions and Side Effects During Rhgh Treatmentmentioning
confidence: 99%
“…About 70% of the patients with NS have short stature (7) although its exact mechanisms have not yet been defined. Multiple studies (8)(9)(10)(11)(12)(13) have shown the effectiveness of growth hormone (GH) treatment for these patients but it is not yet fully standardized.…”
Section: Introductionmentioning
confidence: 99%